Fabrication and functional evaluation of nature-inspired anti-bacterial surfaces - Hawi, Sara (Cranfield University, 2023)
The critical need to develop novel and efficient anti-bacterial strategies, particularly for biomedical implants, serves as a significant motivation for this research. The rise in antibiotic resistance continues to pose a threat to healthcare, making it increasingly important to explore alternative approaches to combat implant-associated surgical site infections (SSIs). These infections arise from bacterial attachment and biofilm formation on the surface of implants and medical devices, leading to costly treatments and high recurrence rates. The present research was aimed at investigating nature-inspired anti-bacterial surfaces through a rigorous fabrication and testing campaign. The study investigated various nanofabrication techniques, such as femtosecond laser ablation, deep reactive ion etching, focused ion beam lithography and scanning probe lithography, for creating nature-inspired sub-micron features on stainless steel and silicon surfaces. The biological response of bacteria (S. aureus) and osteoblast-like cells (MG-63) was evaluated on these surfaces to test antibacterial as well as osseointegration response of the surfaces. S. aureus was chosen due to its high relevance to SSIs and its prevalence in infection and MG-63 cells served as a model for examining the osteoblast behaviour in laboratory studies. The thesis established a novel scale-dependent relationship between surface topography and biological functionality, characterised by the dominating surface wavelength and fractal dimension. The anti-biofouling mechanism was influenced by surface topography, characterised through the fractal dimension, and it was consistently achieved and deemed more suitable for future applications due to the high anti-bacterial efficiency achieved compared to the mechano-bactericidal mechanism. High aspect ratio features (0.056-0.280 µm wavelength, 0.295- 0.765 µm height, 0.045-0.046 µm diameter) did not induce mechano-bactericidal effects on S. aureus NCTC7791, indicating further research is needed. Moreover, the thesis demonstrated a predominant attachment of S. aureus and MG-63 cells on the crystalline silicon surfaces on the (111) orientation. ii For feature sizes below 1 µm, the fractal dimension positively correlated with the anti-bacterial effect and MG-63 cell spreading. For sizes significantly larger than bacterial size (> 2 µm), no correlation was found with the anti-bacterial effect, but surface complexity positively correlated with MG-63 cell spreading. For feature sizes comparable to MG-63 cell size (10-40 µm), cell spreading was inhibited. Femtosecond laser ablation emerged as a promising technique for commercial applications, while scanning probe lithography proved to be a cost-effective, flexible tool for prototyping and research-scale investigations. In conclusion, the development and evaluation of nature-inspired anti-bacterial surfaces have revealed valuable insights into the scale-dependent relationship between surface topography and biological functionality. The findings from this research have the potential to improve the performance and safety of implantable medical devices by reducing the risk of implant-associated SSIs, ultimately benefiting patients and healthcare providers.
Giusca, Claudiu - Associate Supervisor Kumar, Vinod - Associate Supervisor
Keywords: Biomedical implants; nanofabrication; femtosecond laser ablation; deep reactive ion etching; focused ion beam lithography; scanning probe lithography